Analisis Fonologi Autosegmental dalam Proses Penyebaran Fitur Geluncuran Dialek Melayu Saribas (Jurnal Bahasa, 2013)
This study aims to analyse the feature distribution process in the Saribas Malay phonology dialect (SMPD), especially in occuring of glide formation in the vowel sequences when liquids /l,r/ and velar nasal /ŋ/ are in the final position of a word based on autosegmental theory (Goldsmith, 1976, 1990). SMPD data shows that the feature distribution process between segments by taking their features from adjacent segments that resemble the segment. Each segment has a place of articulation and distinctive features that can be distributed onto the adjacent fragment as well as sharing the place of articulation. The default low vowel [a]insertion process occurs when high vowels /i/ and /u/ precede liquids and velar nasal /ŋ/ in the final syllable to form a vowel sequences and thus distributes the glide features from high vowels. This interaction reflects the influences of segmentonto adjacent segment by distributing its feature informing segment with similar identities.Keywords: feature distribution, autosegmental, vowel sequences, glides